Extending the paradigm: a policy framework for healthy and equitable eating (HE2). Issue 18 (20th August 2018) - Pescud, Melanie; Friel, Sharon; Lee, Amanda; Sacks, Gary; Meertens, Elizabeth; Carter, Rob; Cobcroft, Megan; Munn, Elizabeth; Greenfield, Joanne
Abstract: Objective: The current short communication aimed to provide a new conceptualisation of the policy drivers of inequities in healthy eating and to make a call to action to begin populating this framework with evidence of actions that can be taken to reduce the inequities in healthy eating. Design: The Healthy and Equitable Eating (HE 2 ) Framework derives from a systems-based analytical approach involving expert workshops. Setting: Australia. Subjects: Academics, government officials and non-government organisations in Australia. Results: The HE 2 Framework extends previous conceptualisations of policy responses to healthy eating to include the social determinants of healthy eating and its social distribution, encompassing policy areas including housing, social protection, employment, education, transport, urban planning, plus the food system and environment. Conclusions: As the burden of non-communicable diseases continues to grow globally, it is important that governments, practitioners and researchers focus attention on the development and implementation of policies beyond the food system and environment that can address the social determinants of inequities in healthy eating.